Cutaneous Human Papillomavirus E7 Type-Specific Effects on Differentiation and Proliferation of Organotypic Skin Cultures - K. Westphal; B. Akgül; A. Storey; I. Nindl (Cellular Oncology)
Background: A role for cutaneous human β-papillomavirus (HPV) types as co-factors in the development of non-melanoma skin cancer has been postulated. Here we have investigated the effects of E7 expression on keratinocyte differentiation, proliferation and cell-cycle proteins in organotypic skin cultures.